2017
DOI: 10.1111/jdv.14566
|View full text |Cite
|
Sign up to set email alerts
|

The role of β‐blockers in dermatological treatment: a review

Abstract: Many systemic medications have been used off-label in cutaneous diseases. Use of β-adrenergic-blocking agents has risen in popularity among dermatologists since the discovery of their efficacy in treating infantile haemangioma. There has also been an increase in the interest of the applications of β-blockers in other skin disorders. Overall, β-blockers are effective in treating diseases of vascular origin and promote wound healing. They are relatively safe and inexpensive medications that could be included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 83 publications
(131 reference statements)
0
16
0
Order By: Relevance
“…Oral b-blockers might be useful to treat persistent erythema and flushing because they antagonize the effects of sympathetic nerve stimulation and circulating catecholamines at b-adrenoceptors [42][43][44]. In a systematic review including nine studies, Logger and colleagues concluded that oral nonselective b-blockers, especially carvedilol and propranolol, may be an effective treatment option for rosacea-associated facial flushing and erythema [43].…”
Section: Oral Therapiesmentioning
confidence: 99%
“…Oral b-blockers might be useful to treat persistent erythema and flushing because they antagonize the effects of sympathetic nerve stimulation and circulating catecholamines at b-adrenoceptors [42][43][44]. In a systematic review including nine studies, Logger and colleagues concluded that oral nonselective b-blockers, especially carvedilol and propranolol, may be an effective treatment option for rosacea-associated facial flushing and erythema [43].…”
Section: Oral Therapiesmentioning
confidence: 99%
“…β3-AR, that are more sensitive to the action of noradrenaline, are mainly expressed in brown adipose tissue, where they activate lipolysis together with β1-AR, and in skeletal muscle, where they contribute to thermogenesis (Balligand 2013). Beta2-AR are also expressed on skin, where they can be found in secretory coil of apocrine glands, keratinocytes, fibroblasts and melanocytes (Chen and Tsai 2017).…”
Section: Beta-adrenergic System and Pharmacology Of β-Blockersmentioning
confidence: 99%
“…They share the ability to produce potentially severe adverse effects, especially in predisposed areas or areas of locus minoris resistentiae in the skin. Consequent upon review, potential alternatives have been proposed (410).…”
Section: Introductionmentioning
confidence: 99%